Kontroversi Hukuman Mati dan Kebijakan Regulasinya dalam RUU KUHP (Studi Komparatif Menurut Hukum Islam) - M. Abdul Kholiq (Fakultas Hukum Universitas Islam Indonesia, 2007)
The existence of death penalty as a criminal sanction always raises controvertial. Using a comparative study method, this study concludes that : firstly, the existence of death penalty in the draft of Indonesian Criminal Code is to protect the society and to protect the right to live which becomes non-derogable righs. It was designed for specific crime , and it is implemented selectively; secondly, the prohibition of execution before the publict has to be changed and to be reviewed. This mechanism will create an obtacle to achieve the objective of this sanction